Identification of SETBP1 Mutations by Gene Panel Sequencing in Individuals With Intellectual Disability or With “Developmental and Epileptic Encephalopathy” - Leonardi, Emanuela; Bettella, Elisa; Pelizza, Maria Federica; Aspromonte, Maria Cristina; Polli, Roberta; Boniver, Clementina; Sartori, Stefano; Milani, Donatella; Murgia, Alessandra (Frontiers in Neurology, 2020)
SETBP1 alterations are associated with the Schinzel-Giedion syndrome (SGS), characterized by profound neurodevelopmental delay (NDD), typical facial features and multiple congenital malformations (OMIM 269150). Refractory epilepsy is a common feature of SGS. Loss of function (LoF) mutations have been typically associated with a distinct and milder phenotype characterized by intellectual disability (ID) and expressive speech impairment (OMIM 616078). Here we report three rare variants of SETBP1, two novel de novo LoF mutations, identified by NGS analysis of an ID gene panel in 600 NDDs subjects, and one missense identified by a developmental epilepsy gene panel tested in 56 paediatric epileptic cases. The three mutation carrying individuals, who presented mild to severe developmental delay, lacked the cardinal features of classical SGS. One of these subjects, carrying the c.1765C>T (p.Arg589*) mutation, had mild ID with speech delay; the second one carrying the c.2199_2203del (p.Glu734Alafs19*) mutation had generalized epilepsy, responsive to treatment, and moderate ID; the third patient showed a severe ID and had a history of drug resistant epilepsy with West syndrome evolved into a Lennox-Gastaut syndrome. This latter subject carries the missense c.2572G>A (p.Glu858Lys) variant, which is absent from the control population, reported as de novo in a subject with ASD, and located close to the SETBP1 hot spot for SGS-associated mutations. Our findings contribute to further characterizing the associated phenotypes and suggest inclusion of SETBP1 in the list of prioritized genes for the genetic diagnosis of overlapping phenotypes ranging from non-specific ID to “developmental and epileptic encephalopathy” (DEE).